360 CyberKnife Radiosurgery Versus Radiofrequency Thermocoagulation in Patients with Trigeminal Neuralgia With or Without Multiple Sclerosis: A Single-Center Comparison. (1st April 2022) - Loebel, Franziska; Senger, Carolin; Acker, Gueliz; Conti, Alfredo; Vajkoczy, Peter; Budach, Volker; Dengler, Nora
Abstract : INTRODUCTION: Treatment of refractory trigeminal neuralgia (TN), especially in patients with Multiple Sclerosis (MS), remains challenging. Single-fraction Cyberknife radiosurgery (CK) and retrogasserian thermocoagulation (TC) are possible therapeutic options. Comparative studies regarding treatment efficacy and outcome in patients with refractory TN treated with CK or TC, with additional consideration to MS, are scarce. METHODS: Clinical and radiographic data of patients with TN treated with single-fraction CK or TC at a single academic institution were analyzed. Pain level was evaluated using the Barrow Neurological Institute (BNIp) pain scale pre-intervention and 3, 6, 12 months and last follow-up (LFU) post-interventionally. Subgroup analysis was performed in patients with MS. RESULTS: 113 patients were treated with 161 treatments. Median age of the cohort was 61.1 (31.1–98.4) years. There were no significant differences between the cohorts regarding age, side, branch distribution and pre-procedural BNIp. Median follow-up time was 44.3 (3.0–135.9) months. After CK, improved outcome was reported in 59.1%, 57.9%, 66.7%, and 67.3% at 3, 6, 12 months and LFU, while after TC, improved outcome was reported in 85.0%, 77.4%, 70.8% and 55.9%. Patients were more likely to benefit initially and at 3 months follow-up from a TC procedure (p<.0001), but improved outcome at LFU was more pronounced in the CK cohort (p=.077). Repeated treatments were significantly more common in the TC cohort (p=.02). MS was the most frequent neurological co-morbidity. Exclusive analysis of the MS subgroup revealed similar results regarding pain improvement at 3-months follow-up (TC: 95.5% vs. CK: 54.0%; p<.001) and at LFU, (TC: 72% vs. 86.0%; p=.009). Incidence of new-onset hypesthesia was not significantly different in both cohorts (p=.550). CONCLUSION: Both therapies present safe and efficient treatment strategies for patients with refractory TN. Initial BNIp improvement was significantly better in patients treated with TC, while longterm effects were more pronounced in the CK cohort. This was also true for patients with MS.